Mental health and psychological resilience amid the spread of the Omicron variant: a comparison between China and Korea - Chenyuan Qin; Minjung Lee; Jie Deng; Yubin Lee; Myoungsoon You; Jue Liu; Jue Liu; Jue Liu (Frontiers in Public Health)
ObjectivesBesides physical health risks, large public health events also exert negative impacts on people's mental health. We aimed to explore the prevalence and correlates of mental distress and its association with psychological resilience among countries amid the Omicron wave.MethodsWe conducted cross-sectional surveys simultaneously in China and South Korea from March 15 to 30, 2023. Brief Resilience Scale (BRS), Generalized Anxiety Disorder 7-item (GAD-7) scale, and Patient Health Questionnaire-9 (PHQ-9) scale were used to measured psychological resilience and mental distress.ResultsSelf-reported rates of anxiety and depressive symptoms in 3,000 Chinese participants were 24.5% and 30.5%, while the above-mentioned rates were 17.2%and 34.4% in 1,000 Korean participants. Chinese participants had a marginally higher BRS score. Psychological resilience was inversely associated with the prevalence of anxiety symptoms and depressive symptoms. Similar results can be observed in Korea. Results remained robust in all models.ConclusionChinese and Korean populations reported a high prevalence of mental distress with variations in different characteristics, indicating practical implications for developing tailored mental health policies and services in the context of large public health events.